Evaluation of an eLearning teaching innovation to assist clinical radiation therapy educators in the provision of student feedback - Kearney, Maeve; Leech, Michelle (My University, 2021)
Background: Clinical placement is an integral part of the Radiation Therapy undergraduate programme. Feedback and formative assessment during clinical placement are regarded as key to developing clinical skills and competencies.Students regularly report dissatisfaction with the feedback process while clinical educators report heavy clinical workloads and a lack of guidance on feedback mechanisms as barriers to providing meaningful student feedback. Purpose: The purpose of this eLearning intervention was to instruct and support clinical educators involved in giving feedback in the clinical learning environment and to evaluate the impact of the intervention on promoting a culture of feedback in teaching and learning among clinical educators. Methods: An eLearning teaching intervention was developed to support radiation therapists in the provision of student feedback in the clinic.Thematic analysis was used to report attitudes to feedback and feedback practices collected in a pre and a post intervention evaluation. Results: 30 radiation therapists completed the module and pre and post intervention evaluations. Prior to taking the module just over half of respondents stated that they offered regular and ongoing feedback throughout the student’s placement. Positive attitudes to feedback were reported.There was no association found between years of experience supervising students and confidence in providing student feedback. Following completion of the eLearning tool respondents reported a higher level of confidence in the provision of student feedback and almost 70% said the module had changed how they would approach the feedback process by using feedback models in the future. Discussion: Radiation therapists appreciate the structure that using a model in the feedback process offers in the provision of consistent feedback to all students. Good and timely feedback is essential and allows a student opportunity to implement recommended changes to practice and thus improve prior to the end of the placement. It also teaches students how to self-assess and self-reflect-skills that they can use in continuous professional development after they graduate. Conclusion: This eLearning teaching intervention was received favourably by radiation therapists who are key to creating a culture of feedback in the clinical environment that will facilitate students in becoming competent healthcare professionals
Health and Social Care Professions 3rd National (virtual) Conference on Practice Education 17th June 2021 Title: The Evolution of Practice Education: Sharing the Learning
PRESENTED
Hosted by University College Cork - held virtually
Keywords: Cancer; Inclusive Society; International Development; Allied Health Education; Clinical Education; Accessibility